2020
DOI: 10.37624/ijert/13.5.2020.938-942
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Musculoskeletal Discomfort with Body Mass Index (BMI) For Cleaning Workers, Who Work at an Elevated Place

Abstract: The purpose of this research was to determine the extent of the influence of Body Mass Index (BMI) Variations on musculoskeletal discomfort. The steps taken are first to calculate the Body Mass Index (BMI), measure the level of musculoskeletal discomfort of each cleaning worker who works in an elevated place by distributing the Nordic Body Map questionnaire, then perform a statistical test with the Chi-Square Test. The results of this research are painful areas of musculoskeletal discomfort is the left shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Shopkeepers with an overweight body mass index had a 1.09 times greater prevalence of WRMSDs than those with a normal body mass index. Similar findings were found in studies conducted in India [ 70 , 71 ] and Indonesia [ 72 ]. The plausible reason might be that being overweight is one of the health risk factors with the potential to aggravate the occurrence of WRMSD by increasing the physiological and mechanical load on tissues [ 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…Shopkeepers with an overweight body mass index had a 1.09 times greater prevalence of WRMSDs than those with a normal body mass index. Similar findings were found in studies conducted in India [ 70 , 71 ] and Indonesia [ 72 ]. The plausible reason might be that being overweight is one of the health risk factors with the potential to aggravate the occurrence of WRMSD by increasing the physiological and mechanical load on tissues [ 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…Determining the value of Nordic body maps, RULA scores and Asia Pacific reference body mass index [6], normal BMI interval 18.5-24.9 and overweight interval 23.0-24.9 then modified by assessing BMI<22.9 as not obese and BMI>23.0 as obese in respondents in reference to ergonomic chair design.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1, visualization of Musculoskeletal Disorders (MSDs) Cobblers complaints with the highest pain complaint rate of 50%. The findings of Hutabarat [6], Andriani et al [7], Szczygieł et al [8], and Zein et al [9] proved that work activity in sitting conditions has a high level of musculosceletal disorders due to muscle tension. It is mentioned that the need for interlude activities such as rest by standing to straighten the condition of the back [10].…”
Section: Figure 1 Complaint Rate Of Musculoskeletal Disorders (Msds) ...mentioning
confidence: 97%
“…Where the role of a comfortable position for the dominant driver occurs incessant contractions. This is evidence that driving comfort requires constructs of gender, body mass index, height and age which are associated with the point of complaint Nordic body maps [10]. While the findings Oestergaard et al [2], Intani [11], revealed that musculoskeletal disorders are due to high physical work demands and neglect of health due to the dominant driver activity pursuing daily targets.…”
Section: Introductionmentioning
confidence: 99%
“…[22], by conducting a pre test and post test with the results of a decrease in complaints of musculoskeletal discomfort in the left shoulder point area from 80% down to 47%. Findings Hutabarat et al[10], Sofyan and Amir[18], with the statement that the back, waist and hips are indeedthe dominant complaint because they are areas of the body called overus. Statements Houshyar and Kim [23], Pradana et al [24], that the frequency of work with common disorders include back, knees, neck and shoulders.…”
mentioning
confidence: 99%